Cultivation of marine sponges - 曲翊 张卫 李华 虞星炬 (Chinese journal of oceanology and limnology, 2005)
Sponges are the most primitive of multicellular animals, and are major pharmaceutical sources of marine secondary metabolites. A wide variety of new compounds have been isolated from sponges. In order to produce sufficient amounts of the compounds of the needed, it is necessary to obtain large amount of sponges.The production of sponge biomass has become a focus of marine biotechnology.